Issues Of Stock Market Development - G.M. Samandarova (Academia One Publishing, 2024)
The article substantiates that the stock market is an alternative source of business financing in Uzbekistan, the main problem in the stock market is still the insufficient liquidity of shares, that is, the lack of attractive securities that are actively sold and bought on the stock exchange, the views of foreign and local economists are presented on the concept “stock market” and “securities market”, changes in the volume and number of transactions.
Keywords: stock market; securities market; shares